PO195 Outcome measures for duchenne muscular dystrophy: implications for trials. (1st December 2017) - Domingos, Joana; Eagle, Michelle; Moraux, Amelie; Butler, Jordan; Decostre, Valerie; Ridout, Deborah; Mayhew, Anna; Selby, Victoria; Guglieri, Michela; Holst, Menno Van der; Jansen, Merel; Verschuuren, Jan GM; et al.
Abstract : Background: The need for deeper understanding of Duchenne muscular dystrophy (DMD) natural history is supported by the rapid advances in translational research, the increase in clinical trials and outcome of recent studies. Aim: Assess the natural history of DMD through a composite assessment tool encompassing ambulant and non-ambulant phases of the disease. Methods: Multicentre study (5 centres: London, Newcastle, Paris, Leiden, Nijmegen) with a recruitment target of 80-DMD patients assessed 6-monthly according to a shared protocol. Assessments include 6 min walk distance (6 MWD), NorthStar Ambulatory Assessment (NSAA), Performance of Upper Limb (PUL), MyoSet, FVC and whole body DEXA scan (subgroup). Results: We analysed longitudinal data for 79 patients, 39 with >24 months follow-up. Ambulant boys>7 years old declined 2.33 points/year in the NSAA (p<0.001). We observed strong correlations between NSAA and timed tests (6 MWD r=0.85, p<0.001; 10 metre run r=−0.87, p<0.001). Non-ambulant boys lost 3.70 PUL scores/year (p<0.001). PUL total had a strong correlation with myogrip (r=0.77, p<0.001), myopinch (r=0.75, p<0.001) and%FVC (r=0.69, p<0.001). All patients with >45% total lean body mass were ambulant. Conclusion: This on-going study adds to current knowledge on DMD natural history including expected mean changes per year and the relationship between different outcome measures that will contribute to future trial design and interpretation.